Fractal Properties of Various Clay Minerals Obtained from SEM Images. (19th June 2021) - Golsanami, Naser; Fernando, Shanilka Gimhan; Jayasuriya, Madusanka Nirosh; Yan, Weichao; Dong, Huaimin; Cui, Likai; Dong, Xu; Barzgar, Ehsan
Abstract : Clay minerals significantly alter the pore size distribution (PSD) of the gas hydrate-bearing sediments and sandstone reservoir rock by adding an intense amount of micropores to the existing intragranular pore space. Therefore, in the present study, the internal pore space of various clay groups is investigated by manually segmenting Scanning Electron Microscopy (SEM) images. We focused on kaolinite, smectite, chlorite, and dissolution holes and characterized their specific pore space using fractal geometry theory and parameters such as pore count, pore size distribution, area, perimeter, circularity, and density. Herein, the fractal properties of different clay groups and dissolution holes were extracted using the box counting technique and were introduced for each group. It was observed that the presence of clays complicates the original PSD of the reservoir by adding about 1.31-61.30 pores/100  μ m 2 with sizes in the range of 0.003-87.69  μ m 2 . Meanwhile, dissolution holes complicate the pore space by adding 4.88-8.17 extra pores/100  μ m 2 with sizes in the range of 0.06-119.75  μ m 2 . The fractal dimension (D ) and lacunarity (L ) values of the clays' internal pore structure fell in the ranges of 1.51-1.85 and 0.18-0.99, respectively. Likewise, D and L of the dissolution holes were in the ranges of, respectively, 1.63-1.65 and 0.56-0.62. The obtained results of the present study lay the foundation for developing improved fractal models of the reservoir properties which would help to better understand the fluid flow, irreducible fluid saturation, and capillary pressure. These issues are of significant importance for reservoir quality and calculating the accurate amount of producible oil and gas.